Growth and Structural Reforms : A New Assessment - Christiansen, Lone Engbo; Schindler, Martin; Tressel, Thierry (Washington, D.C. : International Monetary Fund, 2009)
This paper presents a simultaneous assessment of the relationship between economic performance and three groups of economic reforms: domestic finance, trade, and the capital account. Among these, domestic financial reforms, and trade reforms, are robustly associated with economic growth, but only in middle-income countries. In contrast, we do not find any systematic positive relationship between capital account liberalization and economic growth. Moreover, the effect of domestic financial reforms on economic growth in middle-income countries is explained by improvements in measured aggregate TFP growth, not by higher aggregate investment. We present evidence that variation in the quality of property rights helps explain the heterogeneity of the effectiveness of financial and trade reforms in developing countries. The evidence suggests that sufficiently developed property rights are a precondition for reaping the benefits of economic reform. Our results are robust to endogeneity bias and a number of alternative specifications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet